Hubungan Komitmen Organisasi dan Kepuasan Kerja Petani sebagai Fasilitator Pembelajaran di Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) Jawa Barat - Ajat Jatnika; Trisakti Haryadi; P. Wiryono (Agrikultura, 2015)
ABSTRACTCorrelation between Organization Commitment and Job Satisfaction of Farmers as Active LearningFacilitators in Farmers‟ Agriculture and Rural Training Centre (FARTC), West JavaThe objective of the reaserach was to describe farmers‟ characteristics as facilitators and to analyzethe correlation of organization commitment and job satisfaction of farmers as facilitators in learningactivities at Farmers‟ Agriculture and Rural Training Centre (FARTC). The kind of research wassurvey that 140 farmers as facilitators in FARTCs located in 17 districs in West Java Provinceinvolved. 89% farmers as facilitators are male; 42,14% of them are 32 – 43 years old; 42,14% ofthem are high schools as their educational background; 74,27% of them have experiences infarming activities; 84,29% of them have experiences as facilitators during 0 – 10 years. This studyapplied the quantitave method namely the correlation analyze. The result of correlation analyzesshows that the organizational commitment has a positive correlation with job satisfaction offarmers as facilitators significantly (ρ < 0.01). The research results recommend that themanagement team of P4S and local government officers to maintain and increase the organizationalcommitment and job satisfaction of farmers as facilitators simultaneously to achieve theeffectiveness of FARTCs.Keywords: Organization commitment, job satisfaction, farmer facilitatorABSTRAKTujuan penelitian adalah mendeskripsikan karakteristik petani fasilitator dan menganalisishubungan komitmen dan kepuasan kerja petani fasilitator pembelajaran di Pusat PelatihanPertanian dan Perdesaan Swadaya (P4S). Jenis penelitian adalah survei dengan melibatkan 140orang petani fasilitator P4S di 17 kabupaten di Jawa Barat. Penelitian menerapkan metodekuantitatif korelasional. Karakteristik petani fasilitator P4S di Jawa Barat diantaranya adalah 89%laki-laki, 40% berusia antara 32-43 tahun, 42,14% berlatar belakang pendidikan formal SLTA/SMK,74,27% memiliki pengalaman berusahatani 0-20 tahun, dan 84,29% menjadi fasilitator 0-10 tahun.Hasil penelitian menunjukkan bahwa komitmen dan kepuasan kerja petani fasilitator memilikihubungan yang signifikan pada taraf signifikansi 0,01. Disarankan baik untuk pengurus internalP4S dan instansi pemerintah sebagai pembina untuk mempertahankan dan meningkatkankomitmen organisasi dan kepuasan kerja petani fasilitator secara simultan dari waktu ke waktuguna mewujudkan P4S yang efektif.Kata Kunci: Komitmen organisasi, kepuasan kerja, petani fasilitator